ANALISIS REPURCHASE INTENTION PADA SMARTPHONE SAMSUNG BERBASIS ANDROID - Mardhiyah Dwi Ilhami; Yulius Wahyu Setiadi ((JEMS) Jurnal Entrepreneur dan Manajemen Sains, 2020)
This study is based on the importance of switching barrier on repurchase intention samsung android based smartphone. Switching barrier consists of switching costs, alternative attractiveness, and interpersonal relationships. This study aims to determine the effect of variable Switching Barrier (Switching Cost, Alternative Attractiveness, Interpersonal Relationship) partially or simultaneously to repurchase intention Samsung Smartphone based on Android In Faculty of Electrical Engineering Department of Engineering University of Bengkulu. Object of this study is the Faculty of Engineering Department of Electrical Engineering University of Bengkulu, which uses samsung android-based smartphones, with accidental sampling method sampling. The number of respondents in this study were 50 people. Methods of data collection using questionnaires. Keywords: Switching Barrier, Repurchase Intention